Effect of Different Culture Conditions on Gene Expression Associated With Cyst Production in Populations of Artemia franciscana - Parraguez, Margarita (Frontiers in Genetics, 2022)
Artemia franciscana inhabits hypersaline environments and has a well-adapted reproductive system to survive in these extreme conditions, represented by the production of diapause cysts. This reproduction mode is controlled by numerous genes that are expressed in response to different environmental stressors, enabling this species to avoid population extinction. To date, the expression of these genes has not been sufficiently studied to clarify their levels in response to combination of different environmental factors under controlled conditions. We analysed the expression of genes related to oviparous reproduction (SGEG, Chitin, Artemin, BCRA1, p8, ArHsp21, ArHsp22 and p26) to determine their association with cyst production in two populations of A. franciscana with contrasting phenotypes, one with high (Barro Negro, BNE, Chile) and one with low (San Francisco Bay, SFB, USA) cyst production. Populations were cultured under controlled conditions of salinity (SAL, 35 and 75 ppt), photoperiod (PHO, 12L:12D and 24L:00D), iron concentration (IC, 0[Fe] and 5[Fe]) and microalgae diet (DIE, D. tertiolecta, DUN and T. suecica, TETRA). Sixteen treatments were performed. Data were recorded daily for nine reproductive parameters per female, including the percent offspring encysted (%) (POE). We analysed the gene expression by semiquantitative RT-PCR. Mean POE was significantly greater in BNE than in SFB (32.40% versus 12.74%, Mann-Whitney, p<0.05). Significant up expression of seven genes in BNE (>2-fold, p<0.05) was observed in 38.28% of treatments. In SFB, the seven genes showed significant differential expression, but most were downregulated in 29.69% of treatments. Multiple regression analyses indicate that in BNE five genes (SGEG, Artemin, Chitin, p8 and BCRA1) and three environmental factors (DIE, SAL and IC) are important predictor variables for POE response variable given that all them were included in the highest ranking models. In SFB, only two genes (ArHsp21 and Artemin) and one environmental factors (SAL) were important explanatory variables in the highest ranking models. It is concluded that the up expression trend in BNE compared to SFB could be a gene expression pattern typical of populations with markedly oviparous reproduction. This gene expression pattern could be useful for monitoring the reproductive mode leading to diapause in Artemia.